2008
DOI: 10.1590/s0074-02762008000400008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activity of meglumine antimoniate produced at Farmanguinhos-Fiocruz, Brazil, against Leishmania (Leishmania) amazonensis, L (L.) chagasi and L (Viannia) braziliensis

Abstract: The leishmanicidal activity of four batches of meglumine antimoniate, produced in Farmanguinhos-Fiocruz, Brazil (TAMs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…The lower susceptibility of L. chagasi is frequently found also with respect to other drugs (Morais-Teixeira et al, 2008;Braga et al, 2007) including the standard drug Amphotericin B (Table 2). The mechanism of action by which EOLC inhibits the parasite growth is still unknown, however some authors (Wink, 2008;Cabral et al, 2009;Laouer et al, 2009) have shown the biological activity of the major compounds present in this EOLC against other eukaryotes parasites and prokaryote microorganisms, which are distant from Leishmania genus, as punctuated before, this work is the first one that demonstrates the activity of EOLC on promastigote culture of Leishmania, so it is relevant to consider some previous studies which enables the construction of few hypothesis to contribute for explanation of EOLC activity on this protozoa culture.…”
Section: Resultsmentioning
confidence: 95%
“…The lower susceptibility of L. chagasi is frequently found also with respect to other drugs (Morais-Teixeira et al, 2008;Braga et al, 2007) including the standard drug Amphotericin B (Table 2). The mechanism of action by which EOLC inhibits the parasite growth is still unknown, however some authors (Wink, 2008;Cabral et al, 2009;Laouer et al, 2009) have shown the biological activity of the major compounds present in this EOLC against other eukaryotes parasites and prokaryote microorganisms, which are distant from Leishmania genus, as punctuated before, this work is the first one that demonstrates the activity of EOLC on promastigote culture of Leishmania, so it is relevant to consider some previous studies which enables the construction of few hypothesis to contribute for explanation of EOLC activity on this protozoa culture.…”
Section: Resultsmentioning
confidence: 95%
“…However, this is somewhat time consuming since the amastigotes must be isolated from infected animals. Alternatively, amastigotes may be obtained by in vitro transformation of promastigotes with minimal changes to the growth conditions and temperature [45]. This method provides effective drug susceptibility assays with persistent infection in macrophages.…”
Section: Classical Methodsmentioning
confidence: 99%
“…This experiment was carried out as described by Morais-Teixeira et al, with some modifications [56]. Hamsters were randomly split into two groups of six animals.…”
Section: Chronic Infection Model Of CL In Golden Hamstermentioning
confidence: 99%